Acute hemolysis after intravenous immunoglobulin amid host factors of ABO‐mismatched bone marrow transplantation, inflammation, and activated mononuclear phagocytes. Issue 3 (5th July 2013) - Michelis, Fotios V.; Branch, Donald R.; Scovell, Iain; Bloch, Evgenia; Pendergrast, Jacob; Lipton, Jeffrey H.; Cserti‐Gazdewich, Christine M.
<x xml:space="preserve">Abstract</x> Background Hemolysis may follow intravenous immunoglobulin (IVIG), with product, dosing, and host factors contributing. The importance of recipient features remains unclear. Case Report A 52‐year‐old obese woman, 10 years after ABO‐mismatched (recipient O, donor A) marrow transplantation, presented with immune thrombocytopenia (ITP). IVIG at 100 g/day × 2 days was followed by hemoglobinuria and angina and dyspnea, with frank hemoglobinemia and anemia (hemoglobin 12.9 to 8.4 over 24 hr, to a nadir of 6.9 g/dL). Study Design and Methods Serologic methods established ABO, A1, Lewis, and Secretor type, while monocyte monolayer assay (MMA) examined erythrophagocytosis with control or patient monocytes, and the implicated IVIG lot to opsonize control (group A1, A2, B, O) or patient red blood cells (RBCs). Baseline, hemolytic, and convalescent markers (including cytokines) were assessed. Results Passive anti‐A was identified on reverse type and eluted from sensitized RBCs (immunoglobulin G 1+, C3d–). Le(a–b+) typing and saliva confirmed H Secretor status. MMA revealed significant activity between patient RBCs, monocytes, and IVIG. However, normal A1 cells opsonized with IVIG were not significantly phagocytosed by either normal or patient monocytes. Proinflammatory markers were significantly elevated before and after IVIG. Conclusions Synergizing host factors (including obesity‐unadjusted dosing and existing inflammation) marked this severe post‐IVIG hemolytic crisis. Group A antigen restriction to myeloid tissues, with H Secretor phenotype, may have contributed, rendering this bone marrow transplant chimera vulnerable to anti‐A in a manner analogous to the idiosyncratic effect of therapeutic anti‐D in certain D+ ITP recipients. However, MMA suggested a macrophage activation state as contributory, perhaps precipitated by existing inflammation.